Siblings, asthma, rhinoconjunctivitis and eczema: a worldwide perspective from the International Study of Asthma and Allergies in Childhood. Issue 1 (January 2015) - Strachan, D. P.; Aït‐Khaled, N.; Foliaki, S.; Mallol, J.; Odhiambo, J.; Pearce, N.; Williams, H. C.; the ISAAC Phase Three Study Group
Summary Background Associations of larger families with lower prevalences of hay fever, eczema and objective markers of allergic sensitization have been found fairly consistently in affluent countries, but little is known about these relationships in less affluent countries. Methods Questionnaire data for 210 200 children aged 6–7 years from 31 countries, and 337 226 children aged 13–14 years from 52 countries, were collected by Phase Three of the International Study of Asthma and Allergies in Childhood (ISAAC). Associations of disease symptoms and labels of asthma, rhinoconjunctivitis and eczema were analysed by numbers of total, older and younger siblings, using mixed (multi‐level) logistic regression models to adjust for individual covariates and at the centre level for region, language and national affluence. Results In both age groups, inverse trends (P < 0.0001) were observed for reported 'hay fever ever' and 'eczema ever' with increasing numbers of total siblings, and more specifically older siblings. These inverse associations were significantly (P < 0.005) stronger in more affluent countries. In contrast, symptoms of severe asthma and severe eczema were positively associated (P < 0.0001) with total sibship size in both age groups. These associations with disease severity were largely independent of position within the sibship and national GNI per capita. Conclusions These global findings on sibship size and childhood asthma, rhinoconjunctivitis and eczema suggest at least two distinct trends. Inverse associations with older siblings (observations which prompted the 'hygiene hypothesis' for allergic disease) are mainly a phenomenon of more affluent countries, whereas greater severity of symptoms in larger families is globally more widespread.